2020
DOI: 10.1002/adfm.202005449
|View full text |Cite
|
Sign up to set email alerts
|

Design of 2D Layered Catalyst by Coherent Heteroepitaxial Conversion for Robust Hydrogen Generation

Abstract: The structural engineering of 2D layered materials is emerging as a powerful strategy to design catalysts for high‐performance hydrogen evolution reaction (HER). However, the ultimate test of this technology under typical operating settings lies in the reduced performance and the shortened lifespan of these catalysts. Here, a novel approach is proposed to design efficient and robust HER catalysts through out‐of‐plane deformation of 2D heterojunction using metal‐organic chemical vapor deposition. High‐yield, si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 54 publications
(75 reference statements)
0
11
0
Order By: Relevance
“…11c). 107 Moreover, the AR-STEM images in Fig. 11d and e present a WTe 2 /WS 2 heterostructure in plan-view and cross-sectional direction.…”
Section: D Compound Materialsmentioning
confidence: 87%
See 3 more Smart Citations
“…11c). 107 Moreover, the AR-STEM images in Fig. 11d and e present a WTe 2 /WS 2 heterostructure in plan-view and cross-sectional direction.…”
Section: D Compound Materialsmentioning
confidence: 87%
“…107 Single-crystalline WTe 2 nanobelts were used as a template for the epitaxial growth of the WTe 2 –WS 2 heterostructure. 107 Interestingly, there were plentiful junctions in the lateral and vertical directions. When the temperature exceeded 700 °C, the curled WS 2 layer generated an epitaxial growth mode, while the layer-by-layer growth manner would occur to form the vital stacking warped layer.…”
Section: D Compound Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Then, Sim et al. demonstrated that eutectic alloy-assisted growth is a promising method for the scalable production of MTMDs-based electrocatalysts, which presents the structural controlled W-based TMDs electrocatalysts with efficient HER activity via this method ( Sim et al., 2021 ).
Figure 6 [Growth of group VIB MTMDs using CVD] (A–E) Phase-controlled synthesis of MoS 2 flakes using potassium.
…”
Section: Introductionmentioning
confidence: 99%